Expression Pattern of Angiogenic Factors in Healthy Heart in Response to Physical Exercise Intensity - Bellafiore, Marianna; Battaglia, Giuseppe; Bianco, Antonino; Palma, Antonio (Frontiers in Physiology, 2019)
Recently many studies showing the regeneration potential of both cardiac and hematopoietic stem cells in adult heart following injury were definitively retracted by the scientific literature. Therefore, stimulating the myocardial angiogenesis becomes to be important for preventing cardiovascular diseases. Regular endurance exercise has been reported to induce capillary growth and be associated to cardioprotective phenotype resulting in an improved defence to metabolic stressors. However, little is known about the crosstalk between healthy skeletal and striated muscle according to the physical exercise intensity. In this study, we examined the expression pattern of vascular endothelial growth factor receptors (VEGFR-1/Flt-1 and VEGFR-2/Flk-1), hypoxia-inducible factor-1α (HIF-1α) and inducible nitric oxide synthase (iNOS) in angiogenic hearts of endurance-trained mice. Sixty-three Swiss male mice were divided into four untrained control groups and three groups trained for 15 (T15), 30 (T30) and 45 (T45) days with a gradually increasing intensity on a treadmill. We observed the localization of all studied proteins with immunostaining and assessed their expression with western blot analyses. We found that VEGFR-2/Flk-1 expression progressively increased in trained hearts compared with the controls, while VEGFR-1/Flt-1 and HIF-1α were higher in T15 mice than controls, T30 and T45 animals. Differently, iNOS levels enhanced after 15 and 30 days of exercise. The results showed that the expression of VEGFR-1/Flt-1, VEGFR-2/Flk-1, HIF-1α and iNOS is differently regulated in striated muscle angiogenesis according the exercise intensity. VEGFR-1/Flt-1 and HIF-1α are up-regulated by a mild exercise intensity, while VEGFR-2/Flk-1 progressively enhances with increasing workload. Differently, iNOS protein is modulated by moderate intensity exercise. VEGF pathway appears to be involved in this regulation mechanism and VEGF might be released by skeletal muscle and act on striated muscle via an endocrine manner. Understanding this relationship is important for developing exercise strategies to protect the heart by insults.